Combined haploidentical and cord blood transplantation for refractory severe aplastic anaemia and hypoplastic myelodysplastic syndrome. (15th May 2021) - Childs, Richard W.; Tian, Xin; Vo, Phuong; Purev, Enkhtsetseg; Kotecha, Ritesh R.; Carlsten, Mattias; Clara, Joseph; Flegel, Willy A.; Adams, Sharon D.; Khuu, Hanh M.; Stroncek, David F.; Cook, Lisa; et al.
Summary: Umbilical cord blood (UCB) transplantation is a potentially curative treatment for patients with refractory severe aplastic anaemia (SAA), but has historically been associated with delayed engraftment and high graft failure and mortality rates. We conducted a prospective phase 2 trial to assess outcome of an allogeneic transplant regimen that co‐infused a single UCB unit with CD34 + ‐selected cells from a haploidentical relative. Among 29 SAA patients [including 10 evolved to myelodysplastic syndrome (MDS)] who underwent the haplo cord transplantation (median age 20 years), 97% had neutrophil recovery (median 10 days), and 93% had platelet recovery (median 32 days). Early myeloid engraftment was from the haplo donor and was gradually replaced by durable engraftment from UCB in most patients. The cumulative incidences of grade II–IV acute and chronic graft‐ versus ‐host disease (GVHD) were 21% and 41%, respectively. With a median follow‐up of 7·5 years, overall survival was 83% and GVHD/relapse‐free survival was 69%. Patient‐ and transplant‐related factors had no impact on engraftment and survival although transplants with haplo‐ versus ‐cord killer‐cell immunoglobulin‐like receptor (KIR) ligand incompatibility had delayed cord engraftment. Our study shows haplo cord transplantation is associated with excellent engraftment and long‐term outcome, providing an alternative option for patients with refractory SAA and hypoplastic MDS who lack human leucocyte antigen (HLA)‐matched donors.